Assessing the system and investor value of utility-scale solar PV. (October 2016) - Ryan, Lisa; Dillon, Joseph; Monaca, Sarah La; Byrne, Julie; O'Malley, Mark
Abstract: With pressure to reduce greenhouse gas emissions from the energy and other sectors, policymakers are increasingly seeking to mobilise investment in renewable electricity with support mechanisms. The objective of this paper is to assess the value of utility-scale solar PV using a multidisciplinary approach. In many cases renewable energy strategies are developed by investors and policymakers on the basis of a relatively narrow analysis of costs. However, as policies should be designed to maximise societal welfare, a wider paradigm is needed in decision-making. This paper argues for an impact assessment of renewable electricity generation that integrates its value from investor, utility, policy maker and end-user perspectives. We propose a multidisciplinary approach to the assessment, combining engineering production cost estimation with financial and market analysis of utility-scale solar PV in Ireland. The results show that while from an investor's perspective solar PV generation is, and will likely remain so for the foreseeable future, relatively expensive in a country with low solar irradiation such as Ireland, there are benefits for the electricity system in terms of reduced wind curtailment and, to a lesser extent, CO2 emissions. This demonstrates why the wider costs and benefits of integrating a renewable electricity technology to the system need to be considered in assessment of renewable policy support mechanism. Policy makers can then seek to maximise the system benefits while minimising the cost of any policy supports.